Central nervous system demyelinating diseases in Hong Kong. Issue 4 (8th March 2021) - Li, Richard; Cheng, Stephen Wing Ho; Chan, Koon Ho; Lau, Alexander Yuk‐Lun; Shiu, Ka Lock; Cheng, Wing Keung; Wu, Shun Ping; Fung, Lai Wah Eva; Ho, Alvin Chi Chung; Liu, Kam Tim; Cherk, Sharon Wan Wah; Yung, Ada Wing Yan; et al.
Abstract: Objective: To give an overview and update on central nervous system inflammatory demyelinating diseases in Hong Kong. Findings: Using retrospective analysis of records from the Multiple Sclerosis (MS) Specialist Panel, the prevalence of MS in Hong Kong was estimated to be 6.9 per 100, 000, while the annual incidence were 0.86 (SD = 0.135, 95% CI = 0.76 to 0.96) and 0.16 (SD = 0.11, 95% CI = 0.08‐0.23) per 100, 000 for adult and pediatric populations, respectively. Preliminary data from the Hong Kong MS Society's NMOSD (neuromyelitis optica spectrum disorders) Registry showed that the local prevalence of NMOSD was 3.3 per 100 000, with a seropositivity rate of 80%. MS and NMOSD both had a female preponderance, and MS had younger disease onset age. NMOSD patients had more long‐term disability in terms of EDSS (expanded disability status scale) but MS patients had more cognitive impairment. Radiological features that discriminated MS and NMOSD were similar to other populations, and brain atrophy was observed in both diseases. The number of available treatment options for MS in Hong Kong has greatly increased in the past decade, including injectables, oral disease‐modifying agents, and immune‐reconstitution therapies. For NMOSD, corticosteroids and oral immunosuppressants were the mainstay of treatment. Summary: The updated prevalence of MS and NMOSD in Hong Kong was higher than previously reported, and comparable with other Asian countries. The clinical, laboratory and imaging features of MS and NMOSD in Hong Kong were similar to those in neighboring regions.